Macroeconomic effects of foreign direct investments on fragile five countries - TURGAN, ERDEM (My University, 2022)
This study investigates the effects of foreign direct investments (FDI) on the export and gross domestic product (GDP) in the original fragile five countries for the period 1990-2017. For the sake of the analysis, annual data is used, and two econometric models are utilized to determine the stationary of variables, their long-term relationship, regression coefficients, and causality relationship between variables. The regression results indicate that a 1% rise in FDI stock increases exports by 0.06% where a 1% rise in imports increases exports by 0.81%. On the other hand, a 1% growth in FDI increases GDP by 0.12% where a 1% rise in exports, increase GDP by 0.79%. The causality test results show that there is a bidirectional relationship between FDI and Imports and GDP, unidirectional relationship from FDI to exports, and bidirectional relationship between GDP and exports.

onezya ve Güney Afrika'da doğrudan yabancı yatırımların, ihracat ve gayri safi yurtiçi hasılaya olan etkileri, 1990-2017 dönemi yıllık verileri kullanılarak, iki farklı ekonometrik model yardımıyla, panel veri analiziyle incelenmiştir. Regresyon sonuçlarına göre doğrudan yabancı yatırım stoku %1 arttığında ortalama %0.06, ithalat %1 arttığında ortalama %0.81 oranında, GSYH’nin ise; doğrudan yabancı yatırım stoku %1 arttığında ortalama %0.12, ihracat %1 arttığında ise ortalama %0.79 oranında artmış olduğu belirlenmiştir. Nedensellik testi sonuçlarına göre doğrudan yabancı yatırımlar ile gayri safi yurtiçi hasıla ve ithalat arasında çift yönlü, doğrudan yabancı yatırımdan ihracata doğru tek yönlü, gayri safi yurtiçi hasıla ile ihracat arasında çift yönlü nedensellik ilişkileri tespit edilmiştir.
Doğrudan yabancı yatırımların kırılgan beşli ülkeleri üzerindeki makro ekonomik etkileri
Keywords: Foreign Direct Investment; Export; Gross Domestic Product; Import; Panel Data Analysis; Doğrudan Yabancı Yatırım; İhracat; Gayri Safi Yurtiçi Hasıla; İthalat; Panel Veri Analizi